Knowledge about the danger signs of pregnancy with pregnancy care behavior in PMB Banjarbaru city - Darmayanti Wulandatika (Health Media, 2021)
Pregnancy care can be used to engage the patient early in pregnancy and provide risk assessment and psychosocial, cultural, and educational support with the ultimate goal of improving pregnancy outcomes. Every woman needs to be aware of the danger signs that occur during pregnancy, because complications from these danger signs are difficult to predict. These danger signs usually indicate the occurrence of obstetric complications that arise during pregnancy, childbirth, or postpartum. Knowledge of these signs and dangers will help you make the right decisions and get the right health services. To prevent more dangerous risks for pregnant women and their fetuses, mothers' knowledge of the signs of pregnancy needs to be increased. This study used an observational, correlational and analytical research design with a cross sectional approach. The results of this study found that there was a relationship between knowledge of danger signs and behavior in pregnancy care, 65 respondents had poor knowledge and behaved poorly towards pregnancy care as many as 19 people (70.4%), had moderate knowledge and behaved well as many as 12 people (54.5%). The result of p-value is 0.034, which means that there is a relationship between knowledge of danger signs and pregnancy care behavior.